1985
DOI: 10.1056/nejm198507183130304
|View full text |Cite
|
Sign up to set email alerts
|

Antibody to Cardiolipin as a Predictor of Fetal Distress or Death in Pregnant Patients with Systemic Lupus Erythematosus

Abstract: During a prospective study of pregnancies in women with systemic lupus erythematosus, we examined the relation between antibody to cardiolipin, measured by the enzyme-linked immunosorbent assay, and midpregnancy fetal distress, identified by abnormal results of antepartum fetal heart-rate testing or by fetal death. All of nine patients with lupus and this complication had abnormally high antibody levels (mean, 212.3 +/- 55.3 units), as compared with values in normal nonpregnant women (28.2 +/- 10.1 units). Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
1
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(74 citation statements)
references
References 28 publications
0
71
1
2
Order By: Relevance
“…Fetal death during the second or third trimester is more specific for aPL-associated fetal loss, but first-trimester spontaneous abortion is not uncommon. It was reported that 8% of women with first-trimester recurrent spontaneous abortions were aCL-positive (5,6). Placental insufficiency due to thrombosis is believed to cause fetal growth retardation, fetal demise, and preterm labor.…”
Section: Recurrent Spontaneous Abortionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal death during the second or third trimester is more specific for aPL-associated fetal loss, but first-trimester spontaneous abortion is not uncommon. It was reported that 8% of women with first-trimester recurrent spontaneous abortions were aCL-positive (5,6). Placental insufficiency due to thrombosis is believed to cause fetal growth retardation, fetal demise, and preterm labor.…”
Section: Recurrent Spontaneous Abortionmentioning
confidence: 99%
“…Antiphospholipid antibodies are strongly associated with clinical complications such as arterial and venous thrombosis (2,3), thrombocytopenia (1,4) and recurrent spontaneous abortions (5,6). The presence of aPL in patient sera in association with these complications has been denoted since 1986 as the antiphospholipid syndrome (APS) (7).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a higher frequency of APA in cases of RSA, especially related to intrauterine fetal growth restriction and preeclampsia [7][8][9][10][11][12]. However, the importance of the APA in RSA remains controversial [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A system of venous collaterals may form around the occlusion that may be seen on imaging as a spider's web. 2,8 Hepatic venography is a reference procedure, but recently this invasive technique to measure venous pressure.…”
mentioning
confidence: 99%
“…1, 3,7,8 The syndrome was described, at first, by Budd and Chiari in 1845 and 1899, respectively and has been mainly reported in East Asia, South Africa, and India. 13,14 The pathogenesis of vascular obstruction is still unclear but some cases of membranous obstruction of the IVC have been reported in Korea, and some cases have been known to have a relationship with oral contraceptive agents 15 or type B viral hepatitis.…”
mentioning
confidence: 99%